ASPEK HUKUM PERLINDUNGAN TERHADAP PENUMPANG BUS DALAM MEWUJUDKAN PERLINDUNGAN KONSUMEN - Rabiah Z. Harahap (DE LEGA LATA: JURNAL ILMU HUKUM, 2016)
Bus is the one of transportation which is often used by society. Society as passenger of bus righteously gains protection. Many of accident happens in public  transportation especially bus that rises a question the important of protection for people as the accicent victim. This question is worthy to be solved because many of public transportation company ignores the passenger’s right. Based on this, government shall take control with presentation of new regulation that aims protection people as consument that uses bus as public transportation.